Optimasi Penjadwalan Produksi Menggunakan Metode Algoritma Nawaz Enscore Ham dan Metode Harmony Search Algorithm Untuk Meminimasi Makespan - Alicia Hamad; Suseno Suseno (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
PT Madubaru is a company engaged in the sugar manufacturing agro-industry. For now the demand for sugar is increasing. But in reality the company has not been able to meet the increasing demand for production resulting in delays to consumers. In 2021 in August the number of sugar sales was 7,758,929 kg, which was previously in July 1,313,720 kg. So it is necessary to change the production schedule using the Nawas Enscore HAM (NEH) Algorithm Method because it is superior compared to other heuristic methods because it is more thorough in calculating the possible sequence of scheduled jobs. And the Harmony Search Algorithm method is proven to be able to reduce or maximize problems in production process scheduling. The makespan value generated by the company's actual method is 67.6 minutes, then the makespan value for the NEH method is 17.6 minutes, and the makespan value for the HSA method is 40 minutes. So that from the production scheduling design, the smallest makespan value is by using NEH with the order of Bulk Sugar-Packed Sugar jobs. Companies can consider their efforts in achieving their company goals, namely by making changes to production scheduling using the Nawaz Enscore Ham Algorithm because the order obtained can minimize completion time.